Construção de um roteiro para um instrumento de coleta de dados para avaliação clínica de pacientes pediátricos hospitalizados - (:unkn) unknown (Universidade Federal do Pampa, 2018)
This work aims to construct a conceptual script for using a data collection instrument for clinical evaluation of pediatric patients. Method: Concept analysis of the Walker and Avant model. To search for evidence in the literature, the narrative modality was used, including the LILACS, MEDLINE, PubMed, SciELO databases, search on Google's Online Service and Software and printed scientific books. Results: 454 nursing variables (phenomena) were conceptualized contained in the instrument of data collection, divided into identification data, anamnesis and physical examination. Final considerations: The analysis of the use of the concepts made it possible to clarify the variables to be evaluated by nurses in clinical practice, supporting the implementation of the stages of the nursing process. Its continuity is suggested, through the clinical and conceptual validation of the instrument and the script, built with a focus on the qualification of nursing care in neonatology and pediatrics.
Construction of a roadmap for a data collection instrument for clinical evaluation of hospitalized pediatric patients
Keywords: Enfermagem; Diagnóstico de enfermagem; Neonatologia; Pediatria; Nursing; Nursing diagnosis; Data collect; Neonatology; Pediatrics; Child; Urgência e emergência; Residência Multiprofissional; CNPQ::CIENCIAS DA SAUDE